Interactive deformation of soft tissues with haptic feedback for medical learning. - Kup-Sze Choi (IEEE Transactions on information technology in biomedicine)
An effective deformable model based on a successive force propagation process is proposed. It avoids the laborious stiffness matrix formulation and is scalable simply by controlling the penetration depth. Mechanical tests are performed to evaluate its feasibility for modeling real tissues. An interactive system is developed using a commercial haptic device.